Controlled synthesis of methacrylate and acrylate diblock copolymers via end-capping using CCTP and FRP. Issue 47 (13th November 2019) - Patias, Georgios; Wemyss, Alan M.; Efstathiou, Spyridon; Town, James S.; Atkins, Christophe J.; Shegiwal, Ataulla; Whitfield, Richard; Haddleton, David M.
Abstract : This work demonstrates a method for preparing acrylic-methacrylic diblock copolymers via end-capping. Abstract : Scalable methods of producing functional materials is of importance. Herein, we report the use of free radical copolymerisation of ω-unsaturated methacrylic macromonomers, as derived from catalytic chain transfer polymerisation (CCTP), with acrylic monomers in solution leading to block copolymers by varying the nature of the macromonomer. We demonstrate the effect that varying the molecular weight and ester side chain length of macromonomer from CCTP, has on the polymerisation leading to either graft or diblock copolymers. DOSY NMR, MALDI-ToF/ToF MS has allowed for the exploration of the extent to which varying the concentration of macromonomer has on the products formed. Importantly, during the successful synthesis of acrylic and methacrylic diblock copolymers with broad dispersities of each block, full consumption of the macromonomers was observed.